Foliar concentration of macro- and micronutrients in four woody legumes from tropical dry-seasonal forest of Costa Rica. - Alvarado, Alfredo (2018)
The information about nutritional aspects of trees in the tropical dry forest is scarce. This investigation aims to establish a normal range of foliar nutrient concentration to four forestry species as related to their growth rates and biological nitrogen fixation capacity in the seasonally dry ecosystem at Guanacaste, Costa Rica. Foliar samples for four species, Dalbergia retusa (cocobolo), Enterolobium cyclocarpum (guanacaste), Hymenaea courbaril (guapinol or jatobá) and Schizolobium parahyba (gallinazo or pachaco), all belonging to the Fabaceae family, were analyzed for N, P, Ca, Mg, K, S, Fe, Mn, Cu, Zn, B and Na. Nutrient concentration varied with species according to their ability to fix nitrogen and their rate of growth. The overall concentration of macronutrients was higher in nitrogen-fixing species compared with non-fixing species, and within each one of those groups, the species with higher growth rate presented more macronutrients than species with low growth rate. According to the concentration of foliar nutrients accumulated in the foliage, we recommend that H. courbaril and D. retusa could be grown in the region soils with medium fertility and E. cyclocarpum and S. parahyba in the more fertile soils. Values ranges of foliar concentrations considered as satisfactory presented in this work are new for D. retusa and H. courbaril and improve the scarce information available for E. cyclocarpum and S. parahyba.